Implementation of Buya Hamka's Thoughts on Student Discipline Character Building in the Era of Society 5.0 - Rahmad Rahmad; Yeni Karneli; Sufyarma Marsidin (Jurnal Psikoedukasi dan Konseling, 2025)
This study aims to analyze the implementation of Buya Hamka's thoughts in the formation of student discipline character, especially in the era of Society 5.0 which is marked by the rapid development of technology. This era brings both challenges and opportunities for education, especially in dealing with the impact of digitalization that affects students' behavior and mindset. Buya Hamka, through his works such as Tafsir Al-Azhar and Di Bawah Lindungan Ka'bah, taught the importance of moral values, discipline, and responsibility in shaping individual character. This research uses the literature study method by linking the principles of discipline according to Buya Hamka with modern technology-based educational approaches. The results show that the moral values promoted by Buya Hamka, such as time discipline, responsibility, and honesty, are very relevant to be applied in the context of education in the era of Society 5.0. The application of these values can improve student discipline and form strong characters, who are not only academically intelligent, but also responsible and moral. This research provides recommendations for educators to integrate Buya Hamka's thoughts in the curriculum and technology-based teaching methods, in order to create a generation that is disciplined, moral, and ready to face the challenges of the times.